2018
DOI: 10.3389/fphys.2018.00954
|View full text |Cite
|
Sign up to set email alerts
|

Development of Swimming Abilities in Squid Paralarvae: Behavioral and Ecological Implications for Dispersal

Abstract: This study investigates the development of swimming abilities and its relationship with morphology, growth, and nourishment of reared Doryteuthis opalescens paralarvae from hatching to 60 days of age. Paralarvae (2.5–11 mm mantle length – ML) were videotaped, and their behavior quantified throughout development using computerized motion analysis. Hatchlings swim dispersed maintaining large nearest neighbor distances (NND, 8.7 ML), with swimming speeds (SS) of 3–8 mm s-1 and paths with long horizontal displacem… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
22
0
4

Year Published

2019
2019
2022
2022

Publication Types

Select...
6

Relationship

2
4

Authors

Journals

citations
Cited by 20 publications
(32 citation statements)
references
References 54 publications
0
22
0
4
Order By: Relevance
“…Paralarvae ranging in size from 2 to 13 mm mantle length (ML) were filmed at 0, 1,2,6,10,11,13,14,17,20,30,40,50,55, and 60 days of age. Mean ML for paralarvae of these ages (0 = 2.65 mm ML, 6 = 2.7 mm ML, 14 = 3.8 mm ML, 20 = 4.1 mm ML, 30 = 4.7 mm ML, 40 = 6.7 mm ML, 55 = 7.8 mm ML, 60 = 9.8 mm ML) were obtained from Vidal et al (2018) as filming used in the present study were conducted simultaneously with the experiments reported in that particular study. A round aquarium (7 cm H, 12 cm diameter and holding a center core of 9 cm) was constructed as a miniature of the large rearing tanks, in which filming was performed from above (dorsal perspective).…”
Section: Rearing Of Paralarvae and Video Recordings Of Predatory Behamentioning
confidence: 99%
See 4 more Smart Citations
“…Paralarvae ranging in size from 2 to 13 mm mantle length (ML) were filmed at 0, 1,2,6,10,11,13,14,17,20,30,40,50,55, and 60 days of age. Mean ML for paralarvae of these ages (0 = 2.65 mm ML, 6 = 2.7 mm ML, 14 = 3.8 mm ML, 20 = 4.1 mm ML, 30 = 4.7 mm ML, 40 = 6.7 mm ML, 55 = 7.8 mm ML, 60 = 9.8 mm ML) were obtained from Vidal et al (2018) as filming used in the present study were conducted simultaneously with the experiments reported in that particular study. A round aquarium (7 cm H, 12 cm diameter and holding a center core of 9 cm) was constructed as a miniature of the large rearing tanks, in which filming was performed from above (dorsal perspective).…”
Section: Rearing Of Paralarvae and Video Recordings Of Predatory Behamentioning
confidence: 99%
“…Arm-crown morphology and predatory behaviors revealed close adjustments with progressive complexity and efficiency as paralarvae go through major developmental milestones. Hatchlings have a rudimentary arm-crown and fins, bell-shaped body, limited swimming abilities (Vidal et al, 2018) and display only a basic predatory behavior (BA). In this behavior, the arms and tentacles frame prey from underneath (Figure 6).…”
Section: Correlated Arm-crown Morphology Predatory Behavior and Prementioning
confidence: 99%
See 3 more Smart Citations